Analisis Perkembangan Implementasi Pendidikan Inklusi Di Indonesia - Azzahra Kamila Cahyani Masdar; Lailatun Nadira; Bayu Sagara; Fardan Ardinata; Wismanto Wismanto (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of the implementation of inclusive education by describing the journey from the initial stages to the present. Through a comprehensive literature review and empirical research, we explore the key factors influencing the implementation of inclusive education, including support from various stakeholders, adequate resource allocation, and a supportive policy framework. This research aims to analyze the development of the implementation of inclusive education. This research method is qualitative research which aims to understand humanitarian and social problems in depth. The results of this research demonstrate the challenges faced by educational practitioners, such as the need for additional training for educators, better integration of students with special needs into the regular curriculum, and the importance of social and emotional support for all students. In addition, we highlight the important role that educational policies play in encouraging or hindering the implementation of inclusive education. By strengthening understanding of the dynamics and complexities of implementing inclusive education, we hope to provide useful insights for practitioners, policy makers and researchers to improve the effectiveness and sustainability of inclusive education throughout the world.